Factors of Empowerment among Women Domestic Workers in Kerala, India: Using Cumulative Empowerment Index and Multiple Regression Model - Dr. G. Jayanthi, Sreeanandan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Women domestic workers are one of the most invisible divisions of workers in the unorganized sector. They are facing adverse social domination and economic discrimination in society. The present study intends to analyze the extent of empowerment take place among the women domestic workers in the study area. The paper evaluated the 200 women domestic workers who living in the two taluk namely Kottayam taluk and Kanjirappally Taluk in Kottayam district, Kerala. Data collected with the help of well-structured interview schedule during a period of 5 months from July 2019 to November 2019. According to the census 2010, this district is the one of the district in Kerala in terms of high number of unorganized sector workers in Kerala. The study explores the different dimensions of empowering factors for women domestic workers, which include (i) social decision, (ii) household decision, (iii) financial decision and (iv) workplace situation. Study used Cumulative Empowerment Index and Multiple Regression Model to analyze the Women domestic workers. Results shows husband seeking domestic workers earns and lack of ownership of permanent assets indicates their subordination in the household hierarchy and highlight that women are partially asserting influence over household properties. Factors like less workplace problems, decision on children’s education and less restriction to visit relatives or friends were greatly influenced their level of empowerment. The index estimates that the majority of the women domestic worker’s level of empowerment is moderate to average.